METAL(II) TETRAFLUOROBORATE COMPLEXES OF SOME DICARBOXYLIC ACID HYDRAZIDES (1990)
Eighty-eight divalent metal complexes derived from dihydrazides of oxalic, malonic, succinic, adipic, phthalic and terephthalic acids, with manganese( 11), cobalt(ll), nickel(ll), copper(IJ), zinc(ll), cadmium(ll), mercury(ll) and magnesium tetrafluoroborates have been prepared. The effect of 1:1 and 1:2 metal to ligand reactant ratios have been examined. The complexes have been characterized on the basis of their analytical data, magnetic susceptibility, electronic and IR spectral studies as well as conductance measurements. Reactions involving 1:1 and 1:2 metal to ligand ratios gave complexes with different metal to ligand stoichiometry in most cases. It is evident, from the analytical data, that complexes precipitated out mostly with 1:2 and 1:3 metal to ligand stoichiometry. However, complexes of oxalic dihydrazide with Cu (II) and Hg (II), succinic dihydrazide with Co (II), Ni(ll), Zn(ll) and Mg prepared using a 1:1 molar reactant ratio contained one and a half moles of ligands. Similarly, complexes of Mn(ll), Ni(ll) and Hg(ll) prepared using a 1:2 molar ratio of metal salt to adipic dihydrazide contained one and a half moles of adipic dihydrazide. Nevertheless, reactions involving 1:1 and 1:2 molar reactant ratios gave the same set of compounds in phthalic dihydrazide with Co(ll), Ni(ll) and Zn(ll) tetrafluoroborates respectively. Likewise the complexes of adipic and malonic dihydrazides with Zn(BF4)2 .6H2O4 and Cd(BF4)2 .7H2O respectively. The complexes have poor solubilities in methanol, ethanol, acetone, nitrobenzene, nitromethane, benzene, hexane, aceto- nitrile, dimethylformamide, dimethylsulfoxide and water. But the complexes of inanganese( 11), cobalt(ll), zinc(ll) and cadmium(II) with oxalic, malonic, succinic and adipic dihydrazides were found to be soluble in water. Similarly, nickel(11), CO ppe-f (11) and magnesium complexes of malonic and succinic dihydrazides were soluble in water, so also is the complex of mercury(ll) with adipic dihydrazide. In addition, the complexes of succinic dihydrazide, with manganesef11) and cadmium(ll) tetrafluoroborates were soluble in dimethylsulfoxide. The infrared spectra indicate that the bonding sites in these compounds are the carbonyl oxygen and the amino or amide nitrogens. The electronic and magnetic data of the complexes of manganese( 11), cobalt(ll), nickel(ll) and copper(ll) at room temperature suggested that they assume octahedral geometry. Generally, for a given ligand, the 1:2 complex has a lower magnetic moment than the 1:3 complex. The Variation of the moments with chain length does not appear to be systematic at room temperature. However, the magnetic moments for the Zn (11), Cd(II), Hg(ll) and Mg indicates that they are diamagnetic with some evidence of polarization paramagnetism. The conductance data of the complexes that were soluble in water and dimethylsulfoxide revealed 1:2 type electrolytes.